А MONOGRAPH OF THE SERBIAN FOLK LITERATURE - Bojović, Jovana D. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
This paper presents a review of the oral tradition of the Serbian people. The author focuses upon the richness of the motives in the oral lyrics, epics and folk tales, pointing out the influences and conditions related to the development of this kind of literature. The results of all classifications referring to the oral literature are demonstrated, as well as the issues of the language, versification and style. The attention is also paid to some of the most beautiful scenes of spiritual life of our people in the past centuries. The content of all the chapters of the monograph entitled “Serbian folk literature” by Vladimir Bovan is systematically presented as well.
Keywords: Vuk Stefanović Karadžić; Serbian literature; oral tradition; Vladimir Bovan; folk literature